2021
DOI: 10.1016/j.jep.2021.114032
|View full text |Cite
|
Sign up to set email alerts
|

Green tea infusion prevents diabetic nephropathy aggravation in recent-onset type 1 diabetes regardless of glycemic control

Abstract: Green tea infusion prevents diabetic nephropathy's aggravation in recent-onset type 1 diabetes regardless of glycemic control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
0
6
0
2
Order By: Relevance
“…The normality was analyzed using the Shapiro–Wilk test. Subsequently, the results were submitted to two separate Student's t -test according to previous studies (Souza et al, 2019; Ladeira et al, 2021). The first analysis evaluated the effectiveness of type 1 diabetes induction comparing healthy animals (negative controls) with STZ-induced diabetic animals (diabetes control).…”
Section: Methodsmentioning
confidence: 99%
“…The normality was analyzed using the Shapiro–Wilk test. Subsequently, the results were submitted to two separate Student's t -test according to previous studies (Souza et al, 2019; Ladeira et al, 2021). The first analysis evaluated the effectiveness of type 1 diabetes induction comparing healthy animals (negative controls) with STZ-induced diabetic animals (diabetes control).…”
Section: Methodsmentioning
confidence: 99%
“…A large population is impacted because DN affects over 1/2 of all diabetic patients during their lifetime and diabetes could be a global epidemic. Due to the complexity of the disease, existing methods of diagnosis and therapy are unable to forestall disease progression or offer a reliable cure [ 22 ]. Today, most renal physiology is regulated by inflammatory chemicals, which makes DN a signal of inflammation.…”
Section: Reviewmentioning
confidence: 99%
“…The components of green tea can interact with proteins participating in cell signaling pathways that regulate energy metabolism, including glucose and glycogen synthesis, glucose reabsorption, hypoxia management (hypoglycemiant capacity), and cell death by apoptosis [ 117 , 118 ]. Such interaction reduces the accumulation of glycogen in the kidney’s proximal tubular cells in diabetes, as well as DNA damage [ 124 ]. A double-blind experiment concerning the treatment of diabetic patients with green tea polyphenols revealed that catechins could reduce podocyte apoptosis and improve kidney function by reducing microalbuminuria [ 125 ].…”
Section: Attenuation Of Secondary Mitochondrial Diseases By Catechinsmentioning
confidence: 99%